I'm viewing the following derivation of a Call Option price using the CRR model. There is one piece of the derivation which I cannot understand.

\begin{align} C_0 &= e^{-rT} \sum_{i=0}^{N} (S_{0}\,u^{N-i}\,d^{i} - K)^{+} \binom {N}{i} q^{N-i}(1-q)^{i}\\ &= e^{-rN \Delta t} \sum_{i=a}^{N} (S_{0}\,u^{N-i}\,d^{i} - K) \binom {N}{i} q^{N-i}(1-q)^{i}\\ &= S_0 \sum_{i=a}^{N} \binom {N}{i} (u\,q\,e^{-r \Delta t})^{N-i}\, (d\,e^{-r \Delta t}\,(1- q))^{i} - Ke^{-rT} \sum_{i=a}^{N} \binom {N}{i} q^{N-i} (1-q)^{i}\\ &= S_0 \sum_{i=a}^{N} \binom {N}{i} \overline{q}^{N-i}\, (1 - \overline{q})^{i} - Ke^{-rT} \sum_{i=a}^{N} \binom {N}{i} q^{N-i} (1-q)^{i}\\ &= S_0 \mathcal{Q}_1 - K e^{-rT} \mathcal{Q}_2 \end{align}

where $\overline{q} = uqe^{-r\Delta t}$.


If $\overline{q} = uqe^{-r\Delta t}$, then I'm assuming $(1-\overline{q}) = d\,e^{-r \Delta t}\,(1- q)$, however I cannot seem to derive this equality.

Appreciate any help understanding why.

Many thanks,



Note that \begin{align*} q= \frac{e^{r\Delta t} -d}{u-d}. \end{align*} Then, \begin{align*} u = \frac{e^{r\Delta t} -d}{q} + d. \end{align*} Therefore, \begin{align*} 1-\bar{q} &= 1-uqe^{-r\Delta t}\\ &=1- \big(e^{r\Delta t} -d\big)e^{-r\Delta t}-dqe^{-r\Delta t}\\ &=de^{-r\Delta t} -dqe^{-r\Delta t}\\ &=de^{-r\Delta t}(1-q). \end{align*}

  • $\begingroup$ Of course it is, how embarrassing. In my defence it's been a long day. Many thanks Gordon, appreciated. $\endgroup$
    – John Smith
    Mar 31 '15 at 17:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.